Analysis of Da’wah Messages in Kadam Sidik Lectures on YouTube: (Study on the Most Realistic Hijrah Strategy Video) - Nurfirdaus, Muhammad Naufal (Tebuireng: Journal of Islamic Studies and Society, 2025)
This study aims to analyze the da’wah message conveyed by Kadam Sidik in his lecture video on YouTube entitled "The Most Realistic Hijrah Strategy". Through a qualitative approach with a content analysis method, this study examines the form of da’wah messages which include the message of faith, sharia, and morals. Data was obtained through observation of the video content and documentation of relevant audience comments. The results of the study show that Kadam Sidik's lectures contain da’wah messages that are educational, reflective, and contextual with the lives of modern society, especially young people. The most dominant da’wah messages are the message of morality, the message of faith, and the message of sharia da’wah which emphasizes the importance of gradual self-change, patience, and istiqamahan in the process of hijrah. Kadam Sidik uses a light, humorous, but still substantial language style, so that the message of da’wah is conveyed effectively and touches the emotional aspects of the audience.